2012
DOI: 10.14507/epaa.v20n37.2012
|View full text |Cite
|
Sign up to set email alerts
|

Funding Disparities and the Inequitable Distribution of Teachers: Evaluating Sources and Solutions

Abstract: Abstract:The inequitable distribution of well-qualified teachers to students in the United States is a longstanding issue. Despite federal mandates under the No Child Left Behind Act and the use of a range of incentives to attract teachers to high-need schools, the problem remains acute in many states. This study examines how and why teacher quality is inequitably distributed, by reviewing research and examining data on school funding, salaries, and teacher qualifications from California and New York-two large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 35 publications
4
90
0
3
Order By: Relevance
“…Both VA and CLASS, as measures of outcome and process quality, are negatively related to the density of students living in poverty in a school (see Table 5). This, too, is congruent with previous research that finds that students in low-income schools receive lower quality instruction and as a result, have lower achievement (Adamson & Darling-Hammond, 2012;Burchinal et al, 2011). At the level of an individual classroom, the relation between classroom quality (CLASS) and teacher quality (VA) was weaker than at the school level (see Table 6).…”
Section: Correlation Of Va and Class For Schools And Teacherssupporting
confidence: 89%
“…Both VA and CLASS, as measures of outcome and process quality, are negatively related to the density of students living in poverty in a school (see Table 5). This, too, is congruent with previous research that finds that students in low-income schools receive lower quality instruction and as a result, have lower achievement (Adamson & Darling-Hammond, 2012;Burchinal et al, 2011). At the level of an individual classroom, the relation between classroom quality (CLASS) and teacher quality (VA) was weaker than at the school level (see Table 6).…”
Section: Correlation Of Va and Class For Schools And Teacherssupporting
confidence: 89%
“…As mentioned above, the manifestations of systemic racism may include inequitable access 816 Educational Administration Quarterly 50 (5) to experienced teachers and college preparatory courses. To this list may be added funding inequalities, disproportionate overcrowding in schools serving some groups of Students of Color, differential access to computer science curriculum, and more (Adamson & Darling-Hammond, 2012;Fanelli et al, 2010;Margolis, 2008). In this study, then, the concept of Third Space must be considered in light of systemic racism in education.…”
Section: Reciprocal Dialogue Third Spaces and Systemic Racismmentioning
confidence: 99%
“…3 If this is so, among those 300,000 teachers that began their teaching careers in 2010, only 90,000 to 150,000 will still be teaching by 2015. Estimates of teacher attrition are substantially higher in schools that serve students of color and English language learners (Adamson & Darling-Hammond, 2012;Jacob, 2007). Excessive teacher turnover is problematic in that it results in lost revenue from the cost of professional development for new teachers and dissolves relationships with families, the community, and the school.…”
Section: Current Problem Focusmentioning
confidence: 99%
“…These researchers have shown that that districts with students of color in low-income schools tend to hire late in the process (Engel, 2009;Levin & Quinn, 2003). The tendency to hire late in summer contributes to the findings that districts with students of color in low-income schools are more likely to have uncertified and/or underprepared teachers as compared to students in predominantly White and more affluent schools (Adamson & Darling-Hammond, 2012;Darling-Hammond, 2010). In other words, the later schools hire, the more likely it is that the most experienced and qualified teachers who are looking for jobs have already accepted positions in other school districts.…”
Section: Social Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation